Pengaruh Labelisasi Hak Pengelolaan Terhadap Eksistensi Hak Ulayat Masyarakat Hukum Adat - Fernando, Dadang; Nur Aisah, Laily; Socialista, Tembang Merah Sunny (Law, Development and Justice Review, 2025)
This study aims to analyze the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 14 of 2024 concerning the Implementation of Land Administration and Registration of Customary Land Rights of Customary Law Communities, which has caused pros and cons in society. Specifically, this study discusses the existence of customary law communities from a normative perspective and the labeling of HPL on customary rights of customary law communities and analyzes the legal consequences of granting HPL to customary law communities over customary rights. This study uses a juridical-normative method. The results of the study conclude that the constitution recognizes the existence of customary law communities along with the customary rights of customary law communities. Regulation of the Minister of ATR/BPN Number 14 of 2024 concerning the Implementation of Land Administration and Registration of Customary Land Rights of Customary Law Communities, although it has provided space for customary land registration, has not provided adequate legal protection for customary law communities in the process of granting Management Rights (HPL). Normative ambiguity and the lack of fair and participatory conflict resolution mechanisms are the main challenges. Therefore, there is a need for revision and strengthening of regulations.